2016
DOI: 10.15421/nvlvet6836
|View full text |Cite
|
Sign up to set email alerts
|

Теоретичні Та Прикладні Аспекти Виробництва М'ясо–рибних Напівфабрикатів

Abstract: Інцертофіли-домінуючий тип екохемоморф мохоподібних степової зони України  МИХАЙЛО ФЕДОСІЙОВИЧ БОЙКО БОЙКО М.Ф., 2010: Інцертофіли-домінуючий тип екохемоморф мохоподібних степової зони України. Чорноморськ. бот. ж., Т.6, № 4: 417-427. У статті підведено підсумок 20-річного вивчення інцертофілів, домінуючого типу екохемоморф мохоподібних степової зони України. У бріофлорі за відношенням мохоподібних до хімізму субстрату відмічено 8 екохеморф, а саме: інцертофіли, кальцефіли, ацидофіли, кальцефоби, кремнєфіли, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Research into development of semi-finished products based on waterfowl duck meat [18,19], and using fish as well [20][21][22], has shown that in terms of their functio nallytechnological and organoleptic characteristics these products are not inferior to those traditional based on pork and beef. However, a possibility for combining these raw materials of regional origin in the formulation of semi-finished products has not been investigated.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Research into development of semi-finished products based on waterfowl duck meat [18,19], and using fish as well [20][21][22], has shown that in terms of their functio nallytechnological and organoleptic characteristics these products are not inferior to those traditional based on pork and beef. However, a possibility for combining these raw materials of regional origin in the formulation of semi-finished products has not been investigated.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Варто зазначити, що рибна сировина у складі фаршевих систем комбінованих м'ясопродуктів здатна сприяти зменшенню втрат під час теплової обробки напівфабрикатів, що робить виробництво м'ясопродуктів більш ефективним без втрати якісних характеристик (Matsuk et al, 2016;Bozhko et al, 2018).…”
Section: вступunclassified
“…Functional-technological properties of combined semi-products with waterfowl poultry are not inferior to traditional analogs [15,16,27], and quality characteristics of meat-containing products using freshwater fish correspond to requirements, regulated by respective standards [17,18].…”
Section: Introductionmentioning
confidence: 99%